Refugee Migration and the Labor Market: Lessons from 40 Years of Post-Arrival Policies in Denmark - Jacob Nielson Arendt; Christian Dustmann; Hyejin Ku (Center for Economic Studies and ifo Institute (CESifo), 2022)
Denmark has accepted refugees from a large variety of countries and for more than four decades. Denmark has also frequently changed policies and regulations concerning integration programs, transfer payments, and conditions for permanent residency. Such policy variation in conjunction with excellent administrative data provides an ideal laboratory to evaluate the effects of different immigration and integration policies on the outcomes of refugee immigrants. In this article, we first describe the Danish experience with refugee immigration over the past four decades. We then review different post-arrival refugee policies and summarize studies that evaluate their effects on the labor market performance of refugees. Lastly, we discuss and contrast these findings in the context of international studies of similar policies and draw conclusions for policy.
Keywords: J22; J24; J61; 330; refugee integration; immigration policies; labor supply; employment; language